2007
DOI: 10.2460/javma.230.5.713
|View full text |Cite
|
Sign up to set email alerts
|

Impact of euthanasia rates, euthanasia practices, and human resource practices on employee turnover in animal shelters

Abstract: Data obtained may suggest several specific avenues that can be pursued to mitigate turnover among employees with euthanasia responsibilities at animal shelters and animal control or veterinary medical organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 10 publications
1
65
1
Order By: Relevance
“…In a situation where the animal is seriously injured or ill with potentially reduced animal welfare, responsible shelter personnel or veterinarian need to consider treatment options or euthanasia. Euthanizing animals was established as a major stressor for personnel in animal shelters where euthanasia is performed on the basis of factors other than behaviour and health reasons (Rogelberg et al 2007;Baran et al 2009;Scotney et al 2015). However, even if euthanasia was performed on medical grounds, concern over animal death was associated with reported traumatic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a situation where the animal is seriously injured or ill with potentially reduced animal welfare, responsible shelter personnel or veterinarian need to consider treatment options or euthanasia. Euthanizing animals was established as a major stressor for personnel in animal shelters where euthanasia is performed on the basis of factors other than behaviour and health reasons (Rogelberg et al 2007;Baran et al 2009;Scotney et al 2015). However, even if euthanasia was performed on medical grounds, concern over animal death was associated with reported traumatic stress.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of shelter cats are euthanized due to overcrowding. The management of unwanted cats, in particular the large-scale euthanasia of often healthy cats, raises ethical issues (Rogelberg et al 2007;Baran et al 2009) and is of increasing concern to the community.…”
mentioning
confidence: 99%
“…Congruent results were identified between this study and previous research which found that euthanasia typically has a negative impact on an individual's health and well-being (Arluke 1991, White and Shawhan 1996, Stamm 1997, Reeve, Spitzmuller et al 2004, Reeve, Rogelberg et al 2005, Rohlf and Bennett 2005. With a survey instrument devised by the researchers, this particular cross-sectional study (Rogelberg, Reeve et al 2007) found a significant correlation between euthanasia rates and employee turnover index (r = 0.36, P < 0.05) that is, higher euthanasia rates were associated with increased employee turnover. Conversely, euthanasia rates for cats were not related to employee turnover.…”
Section: Quantitative Studiesmentioning
confidence: 48%
“…The method of participant recruitment and the way in which data were analysed and reported also varied. Three studies used quantitative methodology (Reeve, Rogelberg et al 2005, Rogelberg, Reeve et al 2007, Black, Winefield et al 2011, five were qualitative studies (Arluke 1991, Reeve, Spitzmuller et al 2004, Rogelberg, DiGiacomo et al 2007, Baran, Allen et al 2009, Davies and Lewis 2010, and four used a mixed-method approach (Rohlf and Bennett 2005, Foster and Maples 2011, Baran, Rogelberg et al 2012, Anderson et al 2013. Two studies were conducted in Australia (Rohlf andBennett 2005, Black, Winefield et al 2011), and one study in the United Kingdom (Davies and Lewis 2010), with the remaining studies conducted in the United States.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation